Challenges and Outcome of Management of Gastroschisis at a Tertiary Institution in North-Eastern Nigeria - Oyinloye, Adewale O.; Abubakar, Auwal M.; Wabada, Samuel; Oyebanji, Lateef O. (Frontiers in Surgery, 2020)
Introduction: Gastroschisis is a congenital anterior abdominal wall defect characterized by herniation of abdominal contents through a defect usually located to the right side of the umbilical cord. It occurs in about 1 in 2,000–4,000 live births and is slightly commoner in males. Management has remained challenging in the low and middle-income countries, with high mortality rates. This study highlights the clinical presentation, treatment, outcomes, and challenges in the management of gastroschisis at a tertiary healthcare center in a resource-limited setting. Methods: This was a retrospective review of the records of all patients with gastroschisis managed over a period of 30 months (January 2016–June 2018). Data on patients' demographics, age, birth weight, clinical presentation, method of gastroschisis reduction and closure, complications, and outcomes were collated. Statistical analysis was performed using SPSS version 20. A p < 0.05 was considered significant. Results: Twenty-four patients with gastroschisis were managed. Of these, 18 patients had data available for analysis. There were 14 males, with a male-female ratio of 3.5:1. The median age at presentation was 11.0 h (range 1–36 h). Ten patients (55.6%) were delivered in a medical facility. One patient had type II jejunal atresia and transverse colonic atresia as associated anomalies. Improvised silos were applied by the bedside in 15 (83.3%) patients, while two patients (11.1%) had primary closure under general anesthesia. One patient died before definitive treatment could be done. Sterile urobags and female condoms were used for constructing improvised silos in 9 (60%) and 6 (40%) patients, respectively. Eight patients who had initial silo application had complete bowel reduction over a median time of 8.0 days (mean 10.0 ± 6.5days, range 2–23 days). Total parenteral nutrition was not available. The average time to commencement of feeding was 8.0 days ± 6.6 (median 6.0 days, range 2–22 days). Full feeding was achieved in five patients (two patients in the primary closure group and three from the silo group) over a mean time of 16.8 days ± 10.4 (median 14.0 days). Sepsis was the commonest complication. Four patients (22.2%) survived. Conclusion: Management of gastroschisis remains challenging in resource-limited regions.